A case of congenital coronary-pulmonary fistulas presenting as spontaneous mediastinal haemorrhage - Thind, Guramrinder Singh (BMJ Case Rep, 2017)
Coronary artery fistulas are rare anomalous vascular connections between coronary arteries and a cardiac chamber or a central vessel, without an intervening capillary bed. Coronary-pulmonary fistulas are a distinct subset of coronary artery fistulas. We present the case of a previously healthy 63-year-old-man who presented with chest pain and was found to have mediastinal haemorrhage. Upon further investigations, he was found to have multiple coronary-pulmonary fistulas with pseudoaneurysm formation in three of the fistulas. Two of these pseudoaneurysms showed inflammatory changes indicative of recent bleed. These were determined to be the source of the mediastinal bleeding and patient’s initial presentation. The patient was managed medically after obtaining multiple expert opinions from various institutions.